Application of Genetic Algorithm to Minimize Harmonic in Multilevel Inverter - Firmansyah Nur Budiman; Novie Ayub Windarko; Son Kuswadi (JURNAL NASIONAL TEKNIK ELEKTRO, 2016)
In inverter design, harmonic voltage is the main issue which affects the performance of the inverter. Generally, the harmonic minimization problem complexity is influenced by the number of harmonic orders to be minimized. This paper presents the utilization of genetic algorithm (GA) to solve harmonic minimization problem in multilevel inverter. The objective is to find relationship between the number of minimized harmonic orders and the results of total harmonic distortion (THD). The inverter to investigate is 11-level, but it is also applicable to multilevel inverters with any number of levels. The results show that harmonic contained in the output voltage has a small dependence on the number of harmonic orders that are minimized. However, the best results are still satisfied even though involving higher number of harmonics. The best-obtained THD, evaluated until 19th harmonic, is 2.76%, which is fairly low and thus acceptable.Keywords : Harmonic, genetic algorithm, multilevel inverter and optimization.Abstrak—Dalam desain inverter, harmonisa tegangan merupakan permasalahan utama yang mempengaruhi performa inverter. Pada umumnya, kompleksitas permasalahan minimisasi harmonisa dipengaruhi oleh jumlah orde harmonisa yang akan diminimisasi. Paper ini membahas utilisasi algoritman genetika untuk menyelesaikan persoalan minimisasi harmonisa di inverter multilevel. Tujuannya adalah untuk menemukan hubungan antara jumlah orde harmonisa yang diminimisasi dan total harmonic distortion (THD) yang dihasilkan. Inverter yang diinvestigasi adalah inverter 11-level, akan tetapi studi ini bisa diaplikasikan ke inverter multilevel dengan jumlah level yang lain. Hasil studi menunjukkan bahwa harmonisa di tegangan keluaran inverter memiliki keterkaitan yang kecil terhadap jumlah orde harmonisa yang diminimisasi. Akan tetapi, hasil yang paling bagus tetap masih didapatkan ketika jumlah harmonisa yang diminimisasi banyak. THD terbaik yang diperoleh, dievaluasi hingga harmonisa ke-19, adalah 2,76%, dimana angka ini cukup kecil dan dapat diterima.Kata Kunci : Harmonisa, algoritma genetika, inverter multilevel dan optimisasi.